Chromatographic Estimation of Water Soluble Vitamins in Wild Edible Plants - Seal, Tapan; Chaudhuri, Kausik; Pillai, Basundhara (Asian Journal of Chemistry, 2021)
A reversed-phase high performance liquid chromatographic technique has been developed for the simultaneous quantitation of water soluble vitamins in 10 potent wild edible plants consumed by the tribal people of North-eastern region in India. The chromatographic separations of vitamins were assessed on Acclaim C18 column using a mobile phase of acetonitrile and aqueous trifluoro acetic acid solution with gradient elution. The experimental results exhibited that for different plants, the vitamin C content ranged between 0.15 ± 0.003 to 8.10 ± 0.03 mg/100g dry plant material (DPM). The vitamin B2 content was determined high in C. album (2.64 ± 0.03 mg/100g DPM) and significant amount of vitamin B9 (1.44 ± 0.03 mg/100g) was detected in E. acuminata. The results showed that these plants are rich sources of vitamins, which can contribute immensely to nutrition and food security. The high percentage of recovery and low limit of detection confirm the suitability of the method for simultaneous estimation of vitamins in these 10 wild edible plants.